Maximizing research opportunities as a trainee in orthopaedics. Issue 1 (January 2019) - Roth, Travis S.; Osbahr, Daryl C.
Abstract : Maximizing research opportunities as a trainee requires genuine scientific curiosity and a strong organizational plan of research execution. Residents or fellows must start early, seek mentorship, and work together to follow through and publish their studies. The purpose of this article is to provide a framework for successful orthopedic research productivity during training, while accounting for the already demanding lifestyle of orthopaedic residents.